2019
DOI: 10.1136/bmjgh-2018-001176
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short-term reconstructive surgical missions: a systematic review

Abstract: IntroductionShort-term missions providing patients in low-income countries with reconstructive surgery are often criticised because evidence of their value is lacking. This study aims to assess the effectiveness of short-term reconstructive surgical missions in low-income and middle-income countries.MethodsA systematic review was conducted according to PRISMA guidelines. We searched five medical databases from inception up to 2 July 2018. Original studies of short-term reconstructive surgical missions were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 84 publications
0
73
0
Order By: Relevance
“…Compared with studies conducted in similar settings, our complication rate also seems high, as such studies report complication rates between 15% and 56%. 28 , 46 , 47 The reason for that may be the strict registration of complications and longer follow-up period of our study. However, even with the complications, surgery was effective.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Compared with studies conducted in similar settings, our complication rate also seems high, as such studies report complication rates between 15% and 56%. 28 , 46 , 47 The reason for that may be the strict registration of complications and longer follow-up period of our study. However, even with the complications, surgery was effective.…”
Section: Discussionmentioning
confidence: 91%
“…Such missions, which provide patients with reconstructive surgical care in LMICs, are often criticized for their lack of quality of care or sustainability, although data to substantiate this are frequently not available. 26 28 , 48 A recent systematic review found 5 studies reporting on contracture release surgery performed during missions. The quality of these studies was indeed generally low, with short-term follow-up and none using ROM as an outcome measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an increasing body of literature outlining the surgical needs of populations in humanitarian settings 3–6. The recognition that the humanitarian sector is not immune from the need to demonstrate safe surgical care has led to calls for more robust outcome data and clearer accountability 7–9. Only few studies, limited by small study size and limited external validity, have addressed the composition of the surgical workforce employed by humanitarian organisations 10 11.…”
Section: Introductionmentioning
confidence: 99%